1997
DOI: 10.1042/bj3270155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thyroid hormone on the tissue-specific expression of cytochrome c oxidase isoforms during cardiac development

Abstract: In mammals, cytochrome coxidase (COX) is composed of 13 different protein subunits. In the rat, two nuclear-encoded subunits, COX VIa and VIII, exist as tissue-specific isoforms: heart and liver. Using Northern-blot analysis, the levels of transcripts for the heart and liver isoforms of VIa and VIII were examined in developing rat hearts. The liver isoform was found to be the predominant form of subunit VIa and the exclusive form of VIII in the 18-day fetal hearts. The mRNA levels of the heart isoform of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“… 22 also reported that the maturation of dihydropyridine receptor (a voltage L type calcium channel) was postponed after the induction of hypothyroidism in fetal and neonate rats and induced ionic imbalance in the heart tissue. In addition, Meehan et al 23 reported that thyroid hormone deficiency in fetal life decreased the level of energy in cardiac cells due to the reduction in the expression of cytochrome c oxidase isoforms and vital enzyme for the production of energy in the electron transport chain in the heart tissue during development period. According to the result from this study and previous reports, it is hence possible for the decrease of cardiac function in the FH rats to be related to the increased expression of β- to α- MHC ratio and deregulation in cytochrome c oxidase isoforms expression and dihydropyridine receptor, all of which could contribute to the power of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“… 22 also reported that the maturation of dihydropyridine receptor (a voltage L type calcium channel) was postponed after the induction of hypothyroidism in fetal and neonate rats and induced ionic imbalance in the heart tissue. In addition, Meehan et al 23 reported that thyroid hormone deficiency in fetal life decreased the level of energy in cardiac cells due to the reduction in the expression of cytochrome c oxidase isoforms and vital enzyme for the production of energy in the electron transport chain in the heart tissue during development period. According to the result from this study and previous reports, it is hence possible for the decrease of cardiac function in the FH rats to be related to the increased expression of β- to α- MHC ratio and deregulation in cytochrome c oxidase isoforms expression and dihydropyridine receptor, all of which could contribute to the power of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Prehybridization and hybridization solutions were prepared according to Kennedy et al (15). All COX and 18S Northern blots were washed according to specific published protocols for individual probes (15,21,23). Both ␣-actin blots were washed 4 ϫ 15 min in 2ϫ sodium saline citrate solution (SSC; 1ϫ SSC ϭ 0.15 M NaCl and 0.015 M sodium citrate), 0.1% sodium dodecyl sulfate (SDS) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The transcript of COX VIa-L is downregulated during development, and the transcript of COX VIa-H is the predominant isoform that is expressed in adult heart and skeletal muscles. This transition also occurs during fetal development in the rat heart (17,23) and during postnatal development in mouse skeletal muscle (16,27). An incomplete isoform transition of COX VIa also occurs during myogenic differentiation in human skeletal muscle cell cultures (33).…”
mentioning
confidence: 99%
“…Modulation of COX activity in the nervous system is directly related to energy demand through neural activity. Signals that affect levels of COX protein in other cell types tend to be related to muscle adaptation or hormonal changes (Kim et al, 1995;Meehan and Kennedy, 1997;Williams, 1986). Understanding COX transcription in neurons, therefore, is important to our ongoing effort to understand the regulation of COX in response to functional demands.…”
Section: Introductionmentioning
confidence: 97%